Study of the bronchoscopic evaluation of patients undergoing bronchoscopy in respiratory medicine department - Roy, Arya; Deshmukh, Hafis; Deshmukh, Ashish; Jadhav, Sunil; Kasat, Shivprasad; Mani, Thamil; S., Thritia (International Journal of Research in Medical Sciences, 2023)
Background: Bronchoalveolar lavage or BAL is a minimally invasive procedure that involves instillation of sterile normal saline into a subsegment of the lung, followed by suction and collection of the instillation for analysis. This procedure is typically facilitated by the introduction of a flexible bronchoscope into a sub-segment of the lung. The purpose of this study was to investigate the pathological variations in the tracheobronchial tree in various respiratory diseases. Methods: The study evaluated the bronchoscopic profile of 150 patients who underwent flexible bronchoscopy in the respiratory medicine department of MGM Medical College in Aurangabad, India from October 2020 to September 2022. Results: The majority of the patients were males (65%) and above the age of 50. The most common reason for bronchoscopy was radiological opacity (80% of cases), followed by diffuse pulmonary infiltration (10%). The study found that bronchoscopy was useful in obtaining samples for diagnosis of various respiratory diseases, including malignancies, tuberculosis, bacterial pneumonia, and hematological malignancies. The study also noted the therapeutic utility of bronchoscopy in managing inoperable stenosis of the central airways. Conclusions: The authors concluded that bronchoscopy is an important diagnostic and therapeutic tool for the management of pulmonary diseases.